2013
DOI: 10.1007/s00268-013-2409-7
|View full text |Cite
|
Sign up to set email alerts
|

Establishment, Characterization and Comparison of Seven Authentic Anaplastic Thyroid Cancer Cell Lines Retaining Clinical Features of the Original Tumors

Abstract: Basic studies using authentic ATC cell lines retaining the clinical features of the original tumor are useful models for investigating the mechanism of anaplastic transformation and exploring novel therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Several cell lines harbor one of these gene mutations. By contrast, OCUT-2 is a unique cell line exhibiting alterations in both B-Raf and PI3KCA genes, resulting in completely aberrant proliferation signal generation independent of EGFR-mediated signaling (9). The results of our previous study may, thus, be interpreted as that the efficacy of EGFR-targeted therapy may be determined by the signaling status downstream of EGFR.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several cell lines harbor one of these gene mutations. By contrast, OCUT-2 is a unique cell line exhibiting alterations in both B-Raf and PI3KCA genes, resulting in completely aberrant proliferation signal generation independent of EGFR-mediated signaling (9). The results of our previous study may, thus, be interpreted as that the efficacy of EGFR-targeted therapy may be determined by the signaling status downstream of EGFR.…”
Section: Discussionmentioning
confidence: 71%
“…OCUT-1-6 were established and characterized in our laboratory. A mutation of B-Raf V600E was found in OCUT-1-5 and a N-Ras mutation was found in the OCUT-6 and ACT-1 cell lines (9 MTT assay. The inhibitory effects of everolimus on the viability of these cell lines were measured by the MTT assay (7).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is a need to develop and characterize novel cell lines that closely recapitulate thyroid cancer pathogenesis. In support of this, new thyroid cancer cell lines have recently been established, including cell lines derived from ATC, PTC, and FTC (15,24,41,42). Here, we report the generation of two new PTC-derived cell lines isolated from pleural effusions (CUTC5, CUTC48), one cell line derived from the primary tumor of a patient with ATC (CUTC60), and a fourth cell line derived from the primary tumor of a patient with metastatic FTC (CUTC61).…”
Section: Discussionmentioning
confidence: 92%
“…However, it has been shown that primary cell cultures better reflect the morphologic and genetic profile of the original tumor and predict response to therapies, compared to commercial cell lines [14][15][16]. Therefore, we used primary endometrioid EC cell cultures to determine the effect of metformin on tumor growth in vivo.…”
Section: Introductionmentioning
confidence: 98%